(untitled) (Web of Teachers: Inderscience Research, 2025)
This article studies the models of the formation of gender culture of students in cooperation with the family and educational institutions. The changes taking place in modern society determine the rapidly developing culture and determine the need to improve the educational process using everything that develops progressive thinking, moral and behavioral models in students. The gender culture of students is characterized by the concept of gender, understanding of the essence and significance of gender characteristics in the life of society, a positive personal attitude towards oneself and society as a carrier of certain gender characteristics.